Youth empowerment programmes in Delta State Nigeria: implication for sustainable development (2020)
This study examines the level of youth awareness, knowledge and involvement in empowerment programmes for sustainable development in Delta State, Nigeria. Three research questions guided this study. Ex-post-facto research design using a multi-stage sampling procedure was used in selecting the samples. The study was carried out in nine Local Government Areas of Delta State, Nigeria with a total of 450 respondents. Three self-designed instruments titled "Youth Awareness and Involvement in Empowerment Programmes for Sustainable Development Questionnaire (YAIEPSDQ) (r = 0.82); Youth Knowledge of Empowerment Programmes for Sustainable Development Questionnaire (YKEPSDQ) (r= 0.73) and Youth Involvement in Empowerment Programmes for Sustainable Development Questionnaire (YIEPSDQ) (r = 0.89) was used to collect data. Data were analysed using frequency counts, percentage, mean and (standard deviation). The findings of this study revealed that youth: were not relatively aware of the empowerment programmes organised by the Delta State government; not duly informed about these programmes; have poor knowledge and are not fully involved in empowerment programmes. It was recommended among other things, that more awareness on youth empowerment programmes should be created, and that the government, non-governmental organisations, and school should take create a conducive environment for the youths to be actively involved in achieving sustainable national development.